Teaching graduate political methodology - Brown, Mitchell; Nordyke, Shane; Thies, Cameron G. (Elgar guides to teaching., 2022)
"Providing expert advice from established scholars in the field of political science, this engaging companion book to Teaching Undergraduate Political Methodology imparts informative guidance on teaching research methods across the graduate curriculum. Written in a concise yet comprehensive style, it illustrates practical and conceptual advice, alongside more detailed chapters focussing on the different aspects of teaching political methodology. Each chapter draws on practised teaching methods covering the what, how and when for teaching political methodology with an in-depth look at systematic research methods. The book is split into four distinct sections for graduate research methods education: the approach, the foundations of research design, quantitative analysis and qualitative analysis. Chapters offer evidence-based advice grounded in the science of teaching and learning (SoTL) literature from experienced, award-winning and highly recognized instructors of political methodology. Teaching Graduate Political Methodology will be required reading for faculty wanting to establish excellent methods for challenging subjects within the fields of political science, public administration and public policies. It will also serve as a useful resource for instructors wishing to gain greater student engagement with their courses by utilising different methods"--